Agente penitenciário: trabalho no cárcere - Santos, Márcia Maria dos (2010)
Behind the high walls of a prison, there is suffering! Suffering from those who atone to their punishment, from those who work on behalf of an alleged regeneration, suffering that has remained for over two centuries. For those who had their conducts characterized as a crime, many studies have been developed. On the other hand, little is known about the prison servants. This research focused mainly on the identification, from the perspective of the correctional officers from two prisons in different states of Brazil, of the negative influence that their jobs have on them, on the factors that serve as protection, as well as the ones that offer them risk. It was observed that hygiene and security conditions are precarious in both prisons. From the reports, scabies, tuberculosis, hepatitis, H1N1, constant violence, politicization of the working environment, doubled working hours, lack of career planning and salaries emerge as evidence of the place where the bodies who work there are subdued, not taking the differences into account. From the above, and as of the many things that still need to be said about this category, it is reiterated the importance in developing studies about the conditions and the work organization and its implications on the mental health of those workers, who lack of public policies committed to their working realities